Neurological Implications of COVID-19 Infections - Needham, Edward J.; Chou, Sherry H.-Y.; Coles, Alasdair J.; Menon, David K. (Neurocritical care, 2020)
The magnitude of the COVID-19 pandemic will result in substantial neurological disease, whether through direct infection (rare), para-infectious complications (less rare), or critical illness more generally (common). Here, we raise the importance of stringent diagnosis and data collection regarding neurological complications of COVID-19; we urge caution in the over-diagnosis of neurological disease where it does not exist, but equally strongly encourage the concerted surveillance for such conditions. Additional to the direct neurological complications of COVID-19 infection, neurological patients are at risk of harm from both structural limitations (such as number of intensive care beds), and a hesitancy to treat with certain necessary medications given risk of nosocomial COVID-19 infection. We therefore also outline the specific management of patients with neuroinflammatory diseases in the context of the pandemic. This article describes the implications of COVID-19 on neurological disease and advertises the Neurocritical Care Society’s international data collection collaborative that seeks to align data elements.